2010
DOI: 10.1037/a0018608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social cognitive and ethnic variables on academic goals of underrepresented students in science and engineering: A multiple-groups analysis.

Abstract: This study investigated the academic interests and goals of 223 African American, Latino/a, Southeast Asian, and Native American undergraduate students in two groups: biological science and engineering (S/E) majors. Using social cognitive career theory (Lent, Brown, & Hackett, 1994), we examined the relationships of social cognitive variables (math/science academic self-efficacy, math/ science outcome expectations), along with the influence of ethnic variables (ethnic identity, othergroup orientation) and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
247
3
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(285 citation statements)
references
References 72 publications
17
247
3
10
Order By: Relevance
“…Por último, en el estudio de McWhirter, Torres, Salgado y Valdez, (2007) la mayoría de los participantes esperaban encontrar barreras económicas y científica influyen en el interés por realizar actividades de dicha rama (H3) y en los intentos por persistir en los estudios científicos (H5). Estos resultados son coincidentes con la mayoría de investigaciones que, además de las H3 y H5, también corroboran la H2 (Blanco, 2011;Byars-Winston et al, 2010;Byars-Winston y Fouad, 2008;Diegelman y Subich, 2001;Ferry, Fouad y Smith, 2000;Gainor y Lent, 1998;Lent et al, 2005;Lent et al, 2011;Lent et al, 2010;Lent, et al, 2007;Schaub y Tokar, 2005;Sheu et al, 2010;Waller, 2006). Asimismo, también se corrobora la H7, pues cuanto más interés manifiesta un estudiante por realizar las actividades de los estudios de la Rama de Ciencias más esfuerzos realiza por persistir en los estudios elegidos, pese a la dificultad asociada a ellos (véase Byars-Winston et al, 2010;Lent et al, 2005;Lent, López et al, 2008;Lent et al, 2011;Lent et al, 2007).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por último, en el estudio de McWhirter, Torres, Salgado y Valdez, (2007) la mayoría de los participantes esperaban encontrar barreras económicas y científica influyen en el interés por realizar actividades de dicha rama (H3) y en los intentos por persistir en los estudios científicos (H5). Estos resultados son coincidentes con la mayoría de investigaciones que, además de las H3 y H5, también corroboran la H2 (Blanco, 2011;Byars-Winston et al, 2010;Byars-Winston y Fouad, 2008;Diegelman y Subich, 2001;Ferry, Fouad y Smith, 2000;Gainor y Lent, 1998;Lent et al, 2005;Lent et al, 2011;Lent et al, 2010;Lent, et al, 2007;Schaub y Tokar, 2005;Sheu et al, 2010;Waller, 2006). Asimismo, también se corrobora la H7, pues cuanto más interés manifiesta un estudiante por realizar las actividades de los estudios de la Rama de Ciencias más esfuerzos realiza por persistir en los estudios elegidos, pese a la dificultad asociada a ellos (véase Byars-Winston et al, 2010;Lent et al, 2005;Lent, López et al, 2008;Lent et al, 2011;Lent et al, 2007).…”
Section: Discussionunclassified
“…Del mismo modo, se han verificado las H4 y H6 porque la valoración que hacen los estudiantes de las consecuencia positivas de finalizar con éxito sus estudios influyen en su interés por las actividades científicas y les ayudan a ser más persistentes para completar con éxito sus estudios (véase Blanco, 2011;Byars-Winston et al, 2010;Byars-Winston y Fouad, 2008;Diegelman y Subich, 2001;Ferry et al, 2000;Fouad et al, 2002;Gainor y Lent, 1998;Huang y Hsieh, 2011;Lent et al, 2001;Lindley, 2005;Sheu et al, 2010;Yeagley et al, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A research agenda for the vocational psychology of agriculture. Australian Journal of Career Development, 24(3), 157-165. doi: 10.1177/1038416215586005 11 In the context of a public policy environment that encourages investments in science, technology, engineering, and mathematics (STEM) careers (e.g., OECD, 2014), vocational psychology research is already making useful contributions to understanding the factors that influence students' choices and efficacy with respect to STEM careers, particularly the interactions among self-efficacy, race, and gender (Byars-Winston, Estrada, Howard, Davis, & Zalapa, 2010;Cordero, Porter, Israel, & Brown, 2010;Lee, Flores, Navarro, & Kanagui-Muñoz, 2015;Lent et al, 2005;Lent et al, 2015). It is conceivable that the extant vocational psychology research into STEM may readily transfer to agriculture.…”
Section: Vocational Psychology Of Agriculturementioning
confidence: 99%
“…It is essential to build and practice these skills early on because postsecondary success is dependent on the habits of mind that students develop, the academic courses they take, and the extracurricular activities they pursue from the beginning of high school. 18 Extracurricular activities, specifically participation in sports teams, provide ample opportunity to develop collaborative and social communication skills. However, participation in sports tend to require motor control and several studies have reported on the motor control difficulties in children with ASD, including how proprioceptive difficulties among children with ASD may contribute to decreased motor planning and to disruptive behaviors that negatively affect their participation in daily tasks.…”
Section: Motivationmentioning
confidence: 99%